Molecular Patching Engineering to Drive Energy Conversion as Efficient and Environment‐Friendly Cell toward Wireless Power Transmission. (21st January 2020) - Shu, Jin‐Cheng; Cao, Mao‐Sheng; Zhang, Min; Wang, Xi‐Xi; Cao, Wen‐Qiang; Fang, Xiao‐Yong; Cao, Mao‐Qing
Abstract: Spatial electromagnetic (EM) radiation, big data, is both an opportunity and a challenge. Harvesting and converting waste EM energy for high‐efficient recycling has a huge significance in the energy field. Herein, a new and effective patching engineering method using conductive polymers to repair magnetic graphene (NF‐P) is proposed, tailoring the microstructure network controllably, including conductive network and relaxation genes. It realizes the precise tuning of EM property, and the EM response shows a significant increase of 52%. The energy transformation inside materials is surveyed, and a revolutionary mode of energy conversion is constructed, ingeniously utilizing the stored electrical energy and the converted heat energy inside the material with the theoretical utilization of absorbed EM energy up to 100%. The NF‐P patching network serves as a prototype for a potential cell device with the EM energy conversion improved by ≈10 times and effective bandwidth increased by 13 GHz that covers the entire research frequency band (2–18 GHz). This research opens up a new idea for energy utilization inside materials, providing a novel and effective path for harvesting, converting and delivering spatial EM energy. Abstract : Energy is not produced, but is simply portered. Here, a revolutionary prototype cell is constructed, ingeniously utilizing the stored electrical energy and converted heat energy inside material with the theoretical utilization of absorbed electromagnetic energy up to 100%.